Violence against men in Mexican and Colombian media: masculinities in question - Lizarralde Díaz, Álvaro (2023)
The results of an investigation are presented whose objective is to analyze the media coverage of violence against men –mainly physical– in Mexican and Colombian newspapers, with the purpose of establishing the visibility and treatment that the selected media give to this type of violence, based on aspects such as length of journalistic texts, genres and sources used, and analysis of the use of language; Furthermore, recognize whether discursive practices constitute forms of symbolic violence that stigmatize masculinity. The approach is qualitative and, for the collection and analysis of information, content analysis is chosen. The type of research is descriptive. It is found that the violence exerted against men constitutes a marginal event in the media agenda, treated as unusual and uncommon. The approach is usually mediated by sexist stereotypes with little depth, since the coverage of violence against men tends to justify it and, in general, presents the attacks in a sensationalist and spectacular way, which places the man as a victim of violence symbolic and cultural violence.